Spremembe v osamljenosti in duševnem zdravju starejših odraslih v času pandemije COVID-19 v primerjavi s predpandemičnim obdobjem, ter vloga uporabe novih tehnologij - Zadravec Šedivy, Nuša (Psihološka obzorja (Ljubljana), 2024)
Loneliness is an important social issue as it affects the quality of life of the older population. It is also one of the most important psychological risk factors for suicide and one of the central concepts related to the circumstances of the COVID-19 pandemic. The aim of our study was to investigate the impact of preventive measures during the COVID-19 pandemic on loneliness and mental health in older adults, as well as the role of the use of new technologies during this period. The study included 221 older adults aged 65-98 years (M = 71.94; SD = 6.70), of whom 55.2% were female. Out of 221 participants, 144 individuals took part in data collection before the COVID-19 pandemic and again during the pandemic, while 77 participants were involved solely in data collection during the COVID-19 pandemic. We examined loneliness, well-being, depression, anxiety and stress, suicide risk, smartphone use and social media use. The results show that on average participants experienced greater emotional loneliness and general feelings of loneliness during the pandemic than before, but there was no significant difference in social loneliness. There was also a higher risk of suicide during the pandemic than before. We have also identified some differences in changes in loneliness and mental health indicators during the pandemic, compared to the pre-pandemic period, based on age, gender, living environment, and household size. In relation to the use of new technologies, e.g. the use of a smartphone and social media, the study also pointed to the negative impact that extensive use could have on feelings of loneliness and mental health. The study addresses the question of the ways in which new technologies are utilized as tools in mental health prevention and highlights the need for the development of specific interventions to address loneliness.
Keywords: duševno zdravje; loneliness; mental health; new technologies; nove tehnologije; older adults; osamljenost; pandemic COVID-19; pandemija COVID-19; starejši odrasli